The Contribution of Supporting Facilitators and Market Drivers in the Development of Business for BTPN Syariah Customers in Banyuwangi: Kontribusi Fasilitator Pendamping dan Penggerak Pasar Daya Dalam Pengembangan Usaha Nasabah BTPN Syariah di Banyuwangi - Aulia Maharani Setyowati Matseri; Noor Rizkiyah; Desita Syafa Kurniasari (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an important sector in increasing national economic growth. The Banyuwangi area, especially Rogojampi and Genteng Districts, has business potential that is worthy of being developed. Mothers who are BTPN Syariah customers as pre-prosperous Micro, Small and Medium Enterprises (MSMEs) are struggling to achieve their families' welfare. The main objective of this activity is to help provide assistance in accessing knowledge, market access, entrepreneurial strategies, and strategies to overcome business obstacles for MSME actors. BTPN Syariah is a bank that focuses on financing without collateral. Productive pre-prosperous mothers, through the Bestee Program in the remote site area, are given a Mentoring Facilitator and Market Power Driver. Mentoring activities by the Mentoring Facilitator include several stages such as location surveys, introductions and assessments, finding obstacles, mentoring, practice, and closing. The stages of mentoring Market Power Drivers are location surveys, interviews, mentoring, documentation, and reporting. The Bestee Program mentoring activities have a positive impact on all parties involved, especially BTPN Syariah customers who participate in the program.